The Amarna Letters: relations between polities in the ancient world - Freire, Lucas G.; Teixeira, Rodrigo Corrêa (Estudos Internacionais: revista de relações internacionais da PUC Minas, 2018)
The Amarna Letters: relations between polities in the ancient world